From fluency to recognition decisions: A broader view of familiarity-based remembering. (September 2020) - Mecklinger, Axel; Bader, Regine
Abstract: The goal of this article is to critically examine current claims and assumptions about the FN400, an event-related potential (ERP) component which has been related to familiarity memory though some uncertainty exists regarding the cognitive processes captured by the FN400. It is proposed that familiarity can be multiply determined and that an important distinction has to be made between a recent-exposure, relative familiarity mechanism indexed by the FN400 and an absolute/baseline familiarity mechanism being reflected by a coincidental but topographically distinct ERP effect. We suggest a broader conceptualization of the memory processes reflected by the FN400 and propose an unexpected fluency-attribution account of familiarity according to which familiarity results from a fast assessment of ongoing processing fluency relative to previous events or current expectations. The computations underlying fluency attribution may be closely related to those characterizing the relative familiarity mechanism underlying the FN400. We also argue that concerted activation of the perirhinal cortex (PrC) and the lateral prefrontal cortex (PFC) plays a pivotal role for fluency attributions and the generation of the FN400. Highlights: The FN400 reflects increments in relative familiarity. Absolute (baseline) familiarity is captured by a coincidental posterior positivity. Familiarity can result from attribution of unexpected fluency to prior occurrence.